Nitrofurantoin-induced pulmonary toxicity: A case report and review of the literature - Wissam K. Kabbara; Melissa C. Kordahi (Elsevier, 2015)
Summary: This paper describes a case of lung injury attributed to the use of Nitrofurantoin and a review of the relevant literature. An 88-year-old woman was admitted to the floor for the evaluation of recent symptoms of dyspnea, fatigue and productive cough. She was initiated on nitrofurantoin 300 mg per day for the treatment of a urinary tract infection 3 days earlier. Upon examination, chest auscultation revealed bilateral inspiratory crackles. Chest radiograph showed bilateral airspace and interstitial infiltrates. Laboratory studies revealed an elevated white blood cell count of 13,500/μL (reference range = 5200-12,400/μL) and blood eosinophilia (10%, reference range: 0-7%). Using clinical judgment and the algorithm of Naranjo, it was determined that nitrofurantoin use was the probable cause of the patient's lung injury. Symptomatic improvement was observed shortly after the drug was discontinued. A review of information from several European and North American pharmacovigilance databases (through June 2014) identified several reports of suspected nitrofurantoin-induced toxicity, including reports of acute toxicity reactions, which were related in many ways to the case we are reporting here. Keywords: Nitrofurantoin, Lung toxicity, Pulmonary toxicity